Avaliação da implantação do currículo de Nutrição da Universidade Federal de Goiás na visão docente - BUENO, Caroline Damásio (2011)
The Federal University of Goiás estabilished in 2009 a new curriculum for nutrition graduation, supporte by the National Curriculum Guidelines for undergraduate courses in Nutrition and the Reorientation National Program in Health Professional Formation. Study conducted to objective was to identify the perceptions of nutritions professors of implantation the new curriculum, by means on qualitative approach. Data were collected from the interview semi-estructured with 12 professors and were analyzed from the thematic content analysis. The study revealed most professors did not clear knowledge of curriculum. The potentialities were: early insertion of students into scenarios for practical since their first year of graduation, active teaching-learning methodologies and insertion of contents on the work world. The limits were: change of students admitted in undergraduate course, inadequate infrastructure of institution education and health services, overload activities, commitment teaching and insecurity with curriculum reformation. Among the strategies of teaching and learning were cited the expository class and the dialogue-based lecture, the seminar, the text study and the problem-solving. The curriculum reform generated a change in strategy with the introduction of active teaching-learning methodologies and case study in a discipline to integrate the basic cycle-professional. Were considered fragilities, the lack pedagogical training of teachers and resistance from students and teachers of active teaching-learning methodologies. The study revealed that that curriculum reformulation has advanced attending to the curricular guidelines and principles for reorientation in health professional formation. Involves administrative, physical and human being factors. More discussion and reflection were indicates that become reality. The study reveal to the requirement for institutional development of teachers in teaching to improve teaching quality. Support to base, enhance and socialize experiences and stimulate news curriculum research.